Fabrication of NiFe2O4@carbon fiber coated with phytic acid-doped polyaniline composite and its application as an electromagnetic wave absorber. Issue 44 (19th August 2019) - Feng, Ailing; Ma, Mingliang; Jia, Zirui; Zhang, Meng; Wu, Guanglei
Abstract : A novel CF@NiFe2 O4 @p-PANI hybrid was designed. Phytic acid-doped polyaniline was applied in the synthesis of an EM wave absorber. The hybrid exhibits excellent EM wave-absorbing performance. Abstract : In this work, a novel CF@NiFe2 O4 composite coated with phytic acid-doped polyaniline (CF@NiFe2 O4 @p-PANI) was facilely synthesized. First, a typical solvothermal reaction was applied to obtain the CF@NiFe2 O4 composite, and then the phytic acid-doped polyaniline was grown in situ on the surface of the CF@NiFe2 O4 composite. The morphological structure, chemical composition, and surface functional group distribution of this hybrid were systematically evaluated. The magnetic saturation ( M s ) value of the hybrid is 29.9 emu g −1, which represents an improvement in the magnetic loss. According to its reflection loss curve, the hybrid exhibits a superior EM wave absorption capacity, with a minimum reflection loss value and effective absorbing bandwidth of −46 dB when the sample thickness is 2.9 mm, and an effective absorption bandwidth of 5 GHz when the sample thickness is 1.5 mm. The excellent performance of this hybrid can mainly be attributed to its ideal matching of magnetic loss and dielectric loss, interfacial polarizations, eddy current loss and interface relaxation. This new material has the potential to be a superior electromagnetic wave absorber or applied as a functional filler to modify resin matrices.